2022
DOI: 10.1021/acs.jcim.2c00851
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Molecule Category of Ligands Targeting the Ligand-Binding Pocket of Nuclear Receptors with Structural Elucidation and Machine Learning

Abstract: The mechanism of transcriptional activation/repression of the nuclear receptors (NRs) involves two main conformations of the NR protein, namely, the active (agonistic) and inactive (antagonistic) conformations. Binding of agonists or antagonists to the ligand-binding pocket (LBP) of NRs can regulate the downstream signaling pathways with different physiological effects. However, it is still hard to determine the molecular type of a LBP-bound ligand because both the agonists and antagonists bind to the same pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…In this study, 11 FXR ligands, including nine agonists (or partial agonists) and two antagonists, were considered for the investigation (Table ). Since the remarkable difference of the active and inactive conformations of an NR protein (especially the Helix-12 region), the conformational selection model is employed as the basis to analyze the dissociation pathway of the investigated ligands, that is, an agonist prefers to bind with the active conformation of a NR protein, while an antagonist favors in binding with the inactive conformation of the protein, , and they bind to the corresponding conformation of a NR protein directly without causing large conformational change of the protein. Twenty repeats of RAMD simulation were conducted for each system to explore the potential dissociation pathways of the FXR ligands.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 11 FXR ligands, including nine agonists (or partial agonists) and two antagonists, were considered for the investigation (Table ). Since the remarkable difference of the active and inactive conformations of an NR protein (especially the Helix-12 region), the conformational selection model is employed as the basis to analyze the dissociation pathway of the investigated ligands, that is, an agonist prefers to bind with the active conformation of a NR protein, while an antagonist favors in binding with the inactive conformation of the protein, , and they bind to the corresponding conformation of a NR protein directly without causing large conformational change of the protein. Twenty repeats of RAMD simulation were conducted for each system to explore the potential dissociation pathways of the FXR ligands.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the antigenic peptides have similar immunological responses as long as their LRIPs are similar. In 2022, Wang et al also found that residue–ligand interaction pattern could reflect not only the binding affinity but also the function of a ligand . Inspired by those successful studies, in this paper, we proposed a novel computational approach that allows us to rationally screen and design agonists that target specific receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Wang et al also found that residue−ligand interaction pattern could reflect not only the binding affinity but also the function of a ligand. 47 Inspired by those successful studies, in this paper, we proposed a novel computational approach that allows us to rationally screen and design agonists that target specific receptors. Considering that CB2 is a promising drug target, which has many indications, and the crystal or cryo-EM structures of active/inactive CB1/CB2 are available, CB1/CB2 is an ideal model system to validate our computational protocol.…”
Section: ■ Discussionmentioning
confidence: 99%